Investigations on Machining of Banana Fibre Reinforced Hybrid Polymer Matrix Composite Materials. (2018) - Sivakiran, G.; Gangwal, Yash; Venkatachalam, G.; Pandivelan, C.; Ayyappan, S.
Abstract: In this investigation, machining of composites, fabricated with randomly oriented chopped banana fiber of length 10 mm as reinforcement and hybrid polymer as matrix, is studied. Two hybrid polymers are used. One is made from 85% of isophthalic polyester and 15% of cashew nut shell liquid and the other is made from 85% of isophthalic polyester and 15% of cardanol. Conventional machining is carried out by taking three parameters (speed, feed and depth of cut) into consideration. Response surface methodology is used for design of experiments. Material removal rate (MRR) and surface roughness are investigated.